Kinetics of trihalomethane formation from organic contaminants in raw water from the Bangkhen water treatment plant - Panyapinyopol B. (2014)
The fractionation of raw water from Bangkhen water treatment plant, Bangkok, Thailand revealed that the mass distribution sequence of the six organic fractions from high to low was hydrophilic neutral (HPIN), hydrophobic acid (HPOA), hydrophilic acid, hydrophobic neutral, hydrophilic base, and hydrophobic base. The main organic matter components in raw water were HPIN and HPOA, which were also the two most important contributors of trihalomethane formation potential (THMFP). Linear dependencies between the level of each organic fraction and the formation potential of THM species were observed, which suggested the reactions between the organic fraction and chlorine during the chlorination were first order. The fractionation led to a deviation of bromide concentration in each organic fraction from the original concentration, and this affected the formation of brominated THM species. However, this effect was demonstrated to be within an acceptable range. The chlorination of an individual organic fraction resulted in a higher level of THMFP than that of the raw water and mixed fractions, indicating an inhibitory effect between the organic species. Copyright © Taylor & Francis Inc.